2009
DOI: 10.1007/s12031-009-9311-7
|View full text |Cite
|
Sign up to set email alerts
|

The Restoration After Repetitive Transcranial Magnetic Stimulation Treatment on Cognitive Ability of Vascular Dementia Rats and Its Impacts on Synaptic Plasticity in Hippocampal CA1 Area

Abstract: The purposes of this research were to study the restoration on the cognitive ability of rat models with vascular dementia (VaD) by repetitive transcranial magnetic stimulation (rTMS) treatment and its impacts on synaptic plasticity in hippocampal CA1 area and to further explore the molecular mechanisms of the rTMS treatment on vascular dementia. Thirty-six male Wistar rats were randomly divided into four groups: the normal control group, the vascular dementia model group, the low-frequency rTMS group, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 41 publications
1
30
0
2
Order By: Relevance
“…A recent study of rTMS in rat models of VaD has reported an improvement of both learning and memory abilities after the administration of low-frequency or high-frequency stimuli. As suggested by the authors, the restoration of cognitive functions could be the result of the biological effects of rTMS that probably acts by promoting the expression of brain-derived neurotrophic factor and other proteins, such as NMDAR1 and synaptophysin, involved in neuronal cell protection, synaptic transmission and brain plasticity [113]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent study of rTMS in rat models of VaD has reported an improvement of both learning and memory abilities after the administration of low-frequency or high-frequency stimuli. As suggested by the authors, the restoration of cognitive functions could be the result of the biological effects of rTMS that probably acts by promoting the expression of brain-derived neurotrophic factor and other proteins, such as NMDAR1 and synaptophysin, involved in neuronal cell protection, synaptic transmission and brain plasticity [113]. …”
Section: Discussionmentioning
confidence: 99%
“…A human study confirmed that after‐effects of rTMS (theta burst stimulation) are linked to the function of the NMDAR 44. Moreover, animal and behavioral studies45, 46, 47, 48, 49 provide compelling evidence that rTMS alters synaptic plasticity of hippocampal areas. Thus, rTMS may be used in order to improve hippocampal function and increase neuronal NMDAR expression.…”
Section: Discussionmentioning
confidence: 81%
“…There is evidence from animal models that rTMS may increase the mRNA and protein expression of NMDAR 43. A human study confirmed that after‐effects of rTMS (theta burst stimulation) are linked to the function of the NMDAR 44.…”
Section: Discussionmentioning
confidence: 88%
“…rTMS at appropriate frequency, intensity, and duration may alter the expression of neurotrophins and their receptors [12, 23, 29, 30], neurotransmitters and their receptors [14, 30-32], and structural proteins [12, 23] in synapses, which in turn affects the postsynaptic depolarization, inducing LTP or LTD and contributing to different cognitive functions.…”
Section: Discussionmentioning
confidence: 99%